A Collaborative Model of Government, Private Sector, and Community in Strengthening the Regional Digital Economy Ecosystem - Mukhtar Galib; Andi Ardasanti; Amiruddin; Aden Gunawan (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study investigates a collaborative model between the government, private sector, and community in strengthening the regional digital economy ecosystem. Digital transformation has become a key driver for regional economic growth, yet disparities in infrastructure, digital literacy, and coordination often hinder inclusive development. The research aims to analyze the roles, challenges, and strategic interventions of each actor in fostering an adaptive and sustainable digital economy. Using a qualitative approach through literature review, this study examines publications from 2018 to 2025, including peer-reviewed journals, government reports, and institutional documents. Data were analyzed using content analysis with thematic coding to identify patterns of cross-sector collaboration, best practices, and policy implications. Findings reveal that effective synergy among government, private sector, and communities accelerates digital adoption, expands market access, and enhances job creation. Key challenges include low digital literacy, unequal infrastructure, and limited alignment of objectives across actors. Strategic recommendations emphasize establishing structured partnership mechanisms, locally tailored digital literacy programs, and shared-value collaboration initiatives. The study contributes to policy and academic discourse by providing a conceptual framework for triple-helix collaboration in regional digital economic development. These insights are valuable for policymakers, practitioners, and researchers aiming to design inclusive, adaptive, and sustainable digital ecosystems at the regional level.